Comparison of the effect of reporting cytoplasmic patterns as anti-nuclear antibody positive and anti-nuclear antibody negative on reflex test ordering - Uyar, Neval Yurttutan (Aktuelle Rheumatologie, 2022)
Objective Anti-nuclear antibody (ANA) patterns are classified as nuclear, cytoplasmic or mitotic. The International Consensus on ANA patterns (ICAP) suggests three parameters for ANA reporting – assay type, results and advice for reflex testing – but has not yet reached a consensus on the reporting of cytoplasmic/mitotic patterns as ANA-negative or positive. We investigated the effect of ICAP’s two proposals for reporting cytoplasmic patterns as ANA-positive and negative with a view to the recommendation for reflex testing in a country that has no national reimbursement policies for automatic reflex testing.Methods This non-interventional descriptive study included 1241 patients with positive cytoplasmic ANA patterns. 442 patients were reported as ANA-negative and 799 as ANA-positive. Patients were followed up for a two-year period to determine testing recommendations based upon nuclear and cytoplasmic patterns. For statistical analysis, the t-test was used, with a significance threshold of p-value<0.05.Results Appropriate reflex orders were seen more commonly with cytoplasmic patterns reported as ANA-positive (27.30%) than with those reported as ANA-negative (5.51%, p-value<0.05). However, ANA-positive reports led to higher ordering of nuclear pattern reflex tests (12.97%) compared with ANA-negative reports (1.10%, p-value<0.05). A large group of patients (59.73% ANA-positive, 93.39% ANA-negative) did not receive reflex testing.Conclusion Reporting cytoplasmic patterns as ANA-positive was considered more significant, but reading the result report without considering the pattern and recommendation notes could lead to inappropriate reflex testing. Besides reaching a consensus for reporting cytoplasmic patterns as ANA-negative or positive, it is important to consider solutions to reimbursement policies for automatic reflex testing to decrease the impediments in reporting cytoplasmic ANA patterns.Hintergrund Antinukleäre Antikörper (ANA) werden als nukleäre, zytoplasmatische oder mitotische Muster klassifiziert. Der internationale Konsens zur ANA-Bestimmung (ICAP) schlägt drei Parameter für die ANA-Berichterstattung vor – die Art des Tests, dessen Ergebnisse und Empfehlungen für Reflextests. Für die Meldung zytoplasmatischer/mitotischer Muster als ANA-negativ oder -positiv wurde jedoch noch kein Konsens erzielt. Wir untersuchten die Auswirkungen der beiden Vorschläge des ICAP für die Meldung von zytoplasmatischen Mustern als ANA-positiv und -negativ auf die Empfehlung für einen Reflextest in einem Land, das über keine nationalen Erstattungsrichtlinien für automatische Reflextests verfügt.Methoden Diese nicht-interventionelle deskriptive Studie umfasste 1241 Patienten mit positiven zytoplasmatischen ANA-Mustern. 442 Patienten wurden als ANA-negativ eingestuft und 799 als ANA-positiv. Zur Ermittlung der Testempfehlungen auf Grundlage der nukleären und zytoplasmatischen Muster wurden die Patienten über einen Zeitraum von zwei Jahren nachbeobachtet. Für die statistische Analyse wurde der t-Test mit einer Signifikanzschwelle von p-Wert<0,05 angewendet.Ergebnisse Ordnungsgemäße Anordnungen von Reflextests wurden häufiger bei zytoplasmatischen Mustern gesehen, die als ANA-positiv angezeigt wurden (27,30%) als bei negativen (5,51%, p-Wert<0,05). Bei ANA-positiven Befunden wurde jedoch häufiger ein Kernmuster-Reflextest angeordnet (12,97%) als bei ANA-negativen Befunden (1,10%, p-Wert<0,05). Bei einer großen Gruppe von Patienten (59,73% ANA-positiv, 93,39% ANA-negativ) wurden keine Reflextests angeordnet.Schlussfolgerung Die Meldung von zytoplasmatischen Mustern als ANA-positiv wurde als aussagekräftiger erachtet. Das Lesen des Ergebnisberichts ohne Berücksichtigung des Musters und der Empfehlungshinweise könnte jedoch zu unangebrachten Reflextests führen. Neben der Erzielung eines Konsenses zur Meldung zytoplasmatischer Muster als ANA-negativ oder -positiv ist es wichtig, Lösungen für die Erstattungsrichtlinien für automatische Reflextests zu prüfen, um die Hindernisse bei der Meldung zytoplasmatischer ANA-Muster zu verringern.
Keywords: cytoplasmic ANA pattern; reflex testing; anti-mitochondrial antibody; autoimmunity; anti-nuclear antibody